Meal‐related oscillations in the serum serotonin levels in healthy young men. (29th January 2018) - Kwon, Obin; Yu, Ji Hee; Jeong, Eunheui; Yoo, Hyun Ju; Kim, Min‐Seon
Summary: Context: Serotonin acts as a neurotransmitter in the central and enteric nervous systems, modulating psychological, metabolic and gastrointestinal functions. Serotonin is also found in the serum or plasma, indicating its potential role as a hormone. Objective: We aimed to assess the 24‐hour diurnal profile of serum serotonin in relation to meal ingestion in healthy adult men. Methods: Ten healthy (5 lean and 5 obese) male subjects were enrolled in this study. Blood samples were drawn every 30‐60 minutes throughout a 24‐hour period to determine the serotonin levels. Three meals were provided on a fixed schedule. To confirm the effect of meal intake on serum serotonin levels, 4 subjects underwent fasting until 1500 h and were then provided a meal without notice. Results: Serum serotonin levels had distinct diurnal variations, with the highest levels early in the morning and the lowest levels in the midafternoon and during sleep. Notably, these diurnal oscillations were markedly reduced in obese subjects. Fluctuations in serum serotonin levels were associated with meal intake, and the levels peaked 30 minutes before meals and exhibited a trough during the postprandial period. Fasting blunted the meal‐related oscillations in serum serotonin levels. Moreover, unexpected meal intake did not lead to a premeal increase in serum serotonin levels. Conclusions: Serum serotonin levels displayed meal‐related diurnal oscillations, which were disrupted by fasting and obesity. These findings suggest the possibility that circulating serotonin modulates metabolic function in humans.